2015
DOI: 10.1093/molbev/msv265
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Identifies Epidermal Proteins Associated with the Evolution of the Turtle Shell

Abstract: The evolution of reptiles, birds, and mammals was associated with the origin of unique integumentary structures. Studies on lizards, chicken, and humans have suggested that the evolution of major structural proteins of the outermost, cornified layers of the epidermis was driven by the diversification of a gene cluster called Epidermal Differentiation Complex (EDC). Turtles have evolved unique defense mechanisms that depend on mechanically resilient modifications of the epidermis. To investigate whether the evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(105 citation statements)
references
References 54 publications
2
103
0
Order By: Relevance
“…The EDCs of the Burmese python ( Python bivittatus ) and the king cobra ( Ophiophagus hannah ) were defined as the genomic regions flanked by S100A genes, like in other amniotes3033. The gene complement of the EDC of these snakes was identified by tBLASTn searches using EDC-encoded proteins of A. carolinensis , chicken and humans as queries and by de novo prediction of genes in an iterative process, as described previously33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDCs of the Burmese python ( Python bivittatus ) and the king cobra ( Ophiophagus hannah ) were defined as the genomic regions flanked by S100A genes, like in other amniotes3033. The gene complement of the EDC of these snakes was identified by tBLASTn searches using EDC-encoded proteins of A. carolinensis , chicken and humans as queries and by de novo prediction of genes in an iterative process, as described previously33.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the dermatologically relevant characterization of human epidermal barrier genes, we have screened non-mammalian tetrapods for homologs of a gene cluster known as the Epidermal Differentiation Complex (EDC)3031323334. Genes encoding S100 fused-type proteins (SFTPs), which are homologous to a subgroup of mammalian EDC genes35, were found in amphibians34, and more complex gene clusters homologous to the mammalian EDC were identified in the chicken3032, in the green anole lizard ( Anolis carolinensis )30 and in turtles33.…”
mentioning
confidence: 99%
“…[11][12][13] Our recent studies have suggested that SFTPs originated prior to the diversification of amniotes (mammals, reptiles and birds). [14][15][16] However, the evolutionary origin of SFTPs has remained uncertain because of incomplete genome data of the next relatives of amniotes, the amphibians. Here, we performed a comparative genomics study to infer the time of origin of SFTPs and to estimate when sequence elements of SFTPs, such as the carboxy-terminal motif implicated in binding keratin filaments, [14,17] have evolved.…”
Section: Questions Addressedmentioning
confidence: 99%
“…Alpha-keratins [5] are widely distributed across all vertebrates, consistent with an early evolutionary origin and comprise an alpha-helical central rod, producing a 10 nm intermediate filament [6]. Beta-keratins (or 'corneous beta-proteins' [7][8][9][10]) are insoluble, rigid, fibrous, structural proteins distinct from alpha-keratins in composition and structure. They are expressed only in reptiles and birds (sauropsids) [11][12][13], suggesting that this gene family originated after the divergence of sauropsids from other vertebrates [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%